The CD40-ATP-P2X7 Receptor Pathway: Cell to Cell Cross-Talk to Promote Inflammation and Programmed Cell Death of Endothelial Cells - Subauste, Carlos S. (Frontiers in Immunology, 2019)
Extracellular adenosine 5’-triphosphate (ATP) functions not only as a neurotransmitter but is also released by non-excitable cells and mediates cell–cell communication involving glia. In pathological conditions, extracellular ATP released by astrocytes may act as a “danger” signal that activates microglia and promotes neuroinflammation. This review summarizes in vitro and in vivo studies that identified CD40 as a novel trigger of ATP release and purinergic-induced inflammation. The use of transgenic mice with expression of CD40 restricted to retinal Müller glia and a model of diabetic retinopathy (a disease where the CD40 pathway is activated) established that CD40 induces release of ATP in Müller glia and triggers in microglia/macrophages purinergic receptor-dependent inflammatory responses that drive the development of retinopathy. The CD40-ATP-P2X7 pathway not only amplifies inflammation but also induces death of retinal endothelial cells, an event key to the development of capillary degeneration and retinal ischemia. Taken together, CD40 expressed in non-hematopoietic cells is sufficient to mediate inflammation and tissue pathology as well as cause death of retinal endothelial cells. This process likely contributes to development of degenerate capillaries, a hallmark of diabetic and ischemic retinopathies. Blockade of signaling pathways downstream of CD40 operative in non-hematopoietic cells may offer a novel means of treating diabetic and ischemic retinopathies.